2023
DOI: 10.3389/fpubh.2023.1148758
|View full text |Cite
|
Sign up to set email alerts
|

Socio-ecological determinants of older people’s mental health and well-being during COVID-19: A qualitative analysis within the Irish context

Abstract: BackgroundEvidence indicates that older people with biological and social vulnerabilities are at high risk of short- and long-term consequences related to the COVID-19 pandemic. However, studies have also highlighted that the crisis may present opportunities for personal growth if older individuals are met with appropriate resources and support.ObjectiveThe aim of this study was to explore the perceptions of older people regarding how individual, social, and environmental factors have supported or hindered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…McLeroy et al ( 50 ) introduced the social-ecological model into health research, noting that behavior is determined by intrapersonal factors, interpersonal processes, primary groups, institutional factors, community factors, and public policies. The socio-ecological model is often used to analyze the influencing factors of health-related factors, such as eating behaviors ( 51 ), physical activity ( 52 ), and mental wellbeing ( 53 ). The socio-ecological model differs from traditional psychological models in that it explicitly combines direct external influences with peripheral factors, making the socio-ecological model popular in the public health realm ( 54 ).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
“…McLeroy et al ( 50 ) introduced the social-ecological model into health research, noting that behavior is determined by intrapersonal factors, interpersonal processes, primary groups, institutional factors, community factors, and public policies. The socio-ecological model is often used to analyze the influencing factors of health-related factors, such as eating behaviors ( 51 ), physical activity ( 52 ), and mental wellbeing ( 53 ). The socio-ecological model differs from traditional psychological models in that it explicitly combines direct external influences with peripheral factors, making the socio-ecological model popular in the public health realm ( 54 ).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
“…Nonetheless, the ability to cope with the stressors brought about by the pandemic was influenced by factors on the micro-, meso-, and macro- levels. On the micro-level, studies have revealed that characteristics like being in good health, previous experiences of adversity, stable financial status, and social networks positively affected individuals' ability to cope with the pandemic (Guzman et al, 2023 ), while having a migration background was associated with increased pandemic-related worry (Ludwig-Dehm et al, 2023 ) and loneliness (Pan et al, 2021 ). At the meso-level, neighborhood parks and nature were positively related to mental and physical health (Bustamante et al, 2022 ; Guzman et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the micro-level, studies have revealed that characteristics like being in good health, previous experiences of adversity, stable financial status, and social networks positively affected individuals' ability to cope with the pandemic (Guzman et al, 2023 ), while having a migration background was associated with increased pandemic-related worry (Ludwig-Dehm et al, 2023 ) and loneliness (Pan et al, 2021 ). At the meso-level, neighborhood parks and nature were positively related to mental and physical health (Bustamante et al, 2022 ; Guzman et al, 2023 ). At the macro-level, stricter physical distancing measures mandated by governments were associated with worse mental health (Mendez-Lopez et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%